Does Successful Use of Digital Learning Materials Predict Teachers’ Intention to Use Them Again in the Future? - Kreijns, Karel; Vermeulen, Marjan; Buuren, Hans van; Acker, Frederik Van (International Review of Research in Open and Distributed Learning, 2017)
Do perceptions of success in using digital learning materials (DLMs) regularly (i.e., several times a week) strengthen (or weaken) teachers’ behavioural intentions to use DLMs again? And which psychological factors have a relationship with the intention to use DLMs again? These questions are important in light of stimulating teacher’s use of DLMs. To answer this question, teacher “flows” were analysed using crosstabs and multinomial logistic regression. These flows visualize how teachers go from a certain degree of perceived success to a certain strength of behavioural intention. Second, Hayes (2013) process method and structured equation modeling (SEM) techniques were applied to determine the mediating role of attitude, perceived norm, and perceived behavioural control of perceived success on the behavioural intention. The results suggested that the teachers’ strength in behavioural intention was in accordance with their perceived success for the case that their self-prediction was positive but that this strength became weaker when teachers’ self-prediction was negative. Attitude and perceived norm mediated the effects only when self-prediction was positive whereas perceived behaviour control did this in both cases. Also, there was a direct effect between perceived success and behavioural intention. It is important that teachers get a chance to experience success with the use of DLMs, enabled either by school leaders (regarding in-service teachers) or by teacher training institutions (regarding pre-service teachers). Only then we will see teachers’ willingness to use DLMs on a regular basis to grow.